Stable isotope compositions of South American camelids in the Dry Puna of Argentina: A frame of reference for the study of prehistoric herding and hunting strategies - Samec, Celeste Tamara (2018)
The prehistoric pastoralist groups that inhabited the Dry Puna of Argentina employed a combination of subsistence strategies that included the herding of domestic South American camelids and the hunting of wild ones since ca. 3500 years BP. The relative importance of both subsistence strategies to the prehistoric economy of these groups can be established through traditional zooarchaeological techniques, although how exactly herding and hunting practices developed and interacted both in space and time remains unknown. The general purpose of this work is to provide a tool to explore these questions through stable isotope analyses of animal tissues. We measured bone collagen δ13C and δ15N values of modern llamas and vicuñas, with the aim to account for the variation in the isotopic compositions of domesticated and wild South American camelids from the Dry Puna of Argentina in order to develop an appropriate frame of reference to address archaeofaunal and paleodietary data. Both δ13C (n = 140, mean = −18.4 ‰) and δ15N (n = 109, mean = +6.3 ‰) values showed a negative and significant correlation with altitude for llamas and vicuñas, which can be explained by the variation identified in plant δ13C and δ15N values and their correlation with altitude, as discussed in previous investigations. Based on these results we elaborated linear regressions models for both δ13C and δ15N values of both species, which will allow us to predict expected δ13C and δ15N values for archaeofaunal materials recovered at archaeological sites using altitude as the explanatory variable.